Longitudinal study of prognostic factors in established periodontitis patients - Machtei, Eli E.; Dunford, Robert; Hausmann, Ernest; Grossi, Sara G.; Powell, Jonathan; Cummins, Diane; Zambon, Joseph J.; Genco, Robert J. (Journal of clinical periodontology, 1997)
Numerous indicators for disease progression have been described in the last decade. The purpose of this study was to examine, longitudinally, a large battery of clinical, microbiological, and immunological indicators, to try to determine whether the presence of one or a combination of these parameters at baseline, would correlate positively with increased attachment and or bone loss (true prognostic factors). Following initial screening, 79 patients with established periodontitis were monitored longitudinally for one year. Whole mouth clinical measurements, plaque gingival and calculus indices, together with pocket depth and attachment level measurements, were repeated every three months. Full mouth radiographic survey, performed at baseline and 12 months, served to determine changes in crestal bone height using an image enhancement technique. Subgingival plaque samples were taken at baseline and every 3 months. Immunofluorescence assays were performed for the a battery of target microorganisms. Serum and GCF samples for IgG subclasses analysis were obtained at each visit and assayed using ELISA techniques. Likewise blood, samples were also drawn at each visit for a quantitative analysis of serum cotinine level. The overall mean attachment loss (AL) and bone loss (BL) were almost identical (0.159 mm and 0.164 mm, respectively). Individual patients variation was large (–0.733 to +1.004 mm). An overall 6.89% of sites were active; individual patients'means ranged from 0–28.9%. Mean pocket depth f PD) showed minimal change over the study period (–0.033 mm) thus suggesting that most if not all the AL was accompanied by concomitant gingival recession. Smokers exhibited greater AL and radiographic BL compared to non‐smokers. Likewise, patients'cotinine level showed direct correlation with outcomes of progressive periodontal breakdown. Past severity of periodontal involvement, as reflected in the patients baseline PD, AL and crestal bone height, showed good correlation with longitudinal changes in the periodontium. This correlation was higher for crestal BL as the outcome variable, while somewhat smaller for change in AL as the outcome variable. Bacteroides forsythus (Bf.), Prevotella intermedia (Pi.) and Porphyromonas gingivalis(Pg.) were frequently found in these patients. The presence of these microorganisms at baseline was associated with further disease progression. Subjects with mean baseline pocket depth equal or greater than 3.2 mm were at greater risk for future bone loss 1 year later (O.R. 2.97; C.I. 1.02‐8.70). Smokers were at significantly greater risk for further attachment loss when compared to non‐smokers (O.R. 5.41; C.I. 1.50‐19.5). Subjects that harbored B. forsythus at baseline, were at seven times greater risk for increased pocket depth (O.R. 7.84; C.I. 1.74–35.3). In conclusion, past periodontal destruction, smoking habits, Bf., Pg., & Pi. are prognostic Factors for further periodontal breakdown. When designing clinical trials, or when evaluating epidemiological data, it is most important to balance for these factors. Also, treatment strategies should attempt to eliminate or modify these factors.